Pharmacokinetics of oral fludrocortisone in septic shock. (22nd August 2016) - Polito, Andrea; Hamitouche, Noureddine; Ribot, Mégane; Polito, Angelo; Laviolle, Bruno; Bellissant, Eric; Annane, Djillali; Alvarez, Jean‐Claude
Abstract : Aim: The combination of hydrocortisone and fludrocortisone improved outcomes in septic shock. However, the specific role of fludrocortisone remains controversial and its pharmacokinetics (PK) has never been investigated in septic shock. This study aimed at characterizing the PK of fludrocortisone in septic shock. Methods: This was a single‐centre ancillary PK study of a large multinational trial of crystalloids versus colloids for acute hypovolemia in intensive care unit (ICU) patients. In 21 adults with septic shock, fludrocortisone plasma concentrations were measured by liquid chromatography–mass spectrometry tandem analysis, before and repeatedly until 18 h after an oral dose of 50 μg. PK parameters were estimated using a nonlinear mixed‐effects modelling. Results: Undetectable plasma concentrations were observed in 7 out of 21 patients. In the remaining 14 patients, plasma fludrocortisone concentrations were best described by a one‐compartmental model with first‐order absorption, a lag time (Tlag ) before the absorption phase, and first‐order elimination. Severity of illness, as quantified by Simplified Acute Physiology Score II, significantly increased Tlag and apparent clearance. There was a large inter‐individual variability in PK parameters. The population estimates of PK parameters (inter‐individual variability) were: Tlag 0.65 h (98%), apparent clearance 40 l h −1 (49%) and apparent volume of distribution 78 l (75%). Plasma half‐life was estimated at 1.35 h (95% CI, 0.84–2.03) and area under the curve of plasma concentrations was estimated at 1.25 μg h l −1 (95% CI, 1.09–1.46). Conclusions: A single oral dose of fludrocortisone yielded undetectable plasma concentrations in one‐third of adults with septic shock. Fludrocortisone PK showed a short plasma elimination half‐life and a large inter‐individual variability.